The DeLone and McLean Model on User Satisfaction of Academic Service Systems - Gurendrawati, Etty; Sasmi, Aji Ahmadi; Ulupui, I Gusti Ketut Agung; Murdayanti, Yunika; Anwar, Choirul; Wahyuningsih, Ika Tri (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
The purpose of this study was to see the perception of the use the educational service system at the Faculty of Economics, Universitas Negeri Jakarta, using the DeLone and McLean model. The samples of this study were final year students and graduate student with a purposive sampling technique and the data obtained through a questionnaire. The data used in this study is cross section panel data, which variables used are system quality, service quality and user satisfaction contained in the DeLone and McLean model. The mixed method made is obtained from the modification of the two models. Finding of result are there is a significant positive effect, between system quality and service quality on user satisfaction. And it was found the analysis there was a need for the development of the current system that can be analyzed using FAST (Framework for the Application of System Thinking), which is carried out in four phases are scope definition, problem analysis, demand analysis, and logical design.